Susceptibility of Staphylococcus spp. isolated from the dog´s skin with recurrent pyoderma (Research, Society and Development, 2021)
Mixed pyogenic infections affect all mammals and their organic systems. Therefore, pyoderma may also be defined as an infectious, pus-producing bacterial condition that affects the skin at any depth level. The present study was composed of 25 dogs with superficial pyoderma that had samples of purulent secretion collected with swab, seeded in culture medium for isolation of Staphylococcus spp. for further evaluation of the antimicrobial susceptibility by the Kirby-Bauer method. Sensitivity to antimicrobials used showed that ciprofloxacin was the drug that showed the highest level of sensitivity (13/25), while the most resistant were Amikacin (19/25), Penicillin (20/25) and Oxacillin (21/25) respectively. The presence of Staphylococcus in infectious processes in animals has been increasingly frequent, and antimicrobial resistance is emerging.